Prostate tumor growth is impaired by CtBP1 depletion in high-fat diet-fed mice - Moiola, Cristian Pablo (2014)
Clinical and epidemiologic data suggest that obesity is associated with more aggressive forms of prostate cancer, poor prognosis, and increased mortality. C-terminal-binding protein 1 (CtBP1) is a transcription repressor of tumor suppressor genes and is activated by NADH binding. High calorie intake decreases intracellular NAD(+)/NADH ratio. The aim of this work was to assess the effect of high-fat diet (HFD) and CtBP1 expression modulation over prostate xenograft growth. We developed a metabolic syndrome-like disease in vivo model by feeding male nude mice with HFD during 16 weeks. Control diet (CD)-fed animals were maintained at the same conditions. Mice were inoculated with PC3 cells stable transfected with shCtBP1 or control plasmids. Genome-wide expression profiles and Gene Set Enrichment Analysis (GSEA) were performed from PC3.shCtBP1 versus PC3.pGIPZ HFD-fed mice tumors.